2002
DOI: 10.1001/archinte.162.13.1493
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Urological Symptoms in a Cohort of Users of the HIV Protease Inhibitor Indinavir Sulfate<subtitle>The ATHENA Cohort</subtitle>

Abstract: Increased alertness for urological symptoms is warranted for patients starting indinavir treatment, particularly among those with a low lean body mass, during indinavir regimens of 1000 mg or more twice daily, and in warm weather environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…Of these, seven (3%) had nephrolithiasis and the other 12 (5%) had crystalluria associated with dysuria or with back or flank pain (of 40 patients who were not receiving indinavir, none had similar crystals). In a study of 1219 patients, including 644 individuals treated with indinavir, Dieleman et al [41] estimated at 8.3 per 100 treatment-years the incidence of indinavir-related urologic/nephrologic symptoms (nephrolithiasis, renal colic, flank pain, hematuria, renal failure, or nephropathy) versus 0.8 per 100 treatment-years for other HIV protease inhibitors. The incidence of renal colic was prospectively estimated at 23.6% over 2 years in a cohort of 555 patients treated with a HAART regimen, including indinavir [42].…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…Of these, seven (3%) had nephrolithiasis and the other 12 (5%) had crystalluria associated with dysuria or with back or flank pain (of 40 patients who were not receiving indinavir, none had similar crystals). In a study of 1219 patients, including 644 individuals treated with indinavir, Dieleman et al [41] estimated at 8.3 per 100 treatment-years the incidence of indinavir-related urologic/nephrologic symptoms (nephrolithiasis, renal colic, flank pain, hematuria, renal failure, or nephropathy) versus 0.8 per 100 treatment-years for other HIV protease inhibitors. The incidence of renal colic was prospectively estimated at 23.6% over 2 years in a cohort of 555 patients treated with a HAART regimen, including indinavir [42].…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…People with human immunodeficiency virus (HIV) infection have an increased risk for kidney disease for a variety of reasons, including the high prevalence of hepatitis B and C co-infection [1][2][3] , drug abuse 4 , direct effects of HIV on kidney cells [5][6][7][8][9] and nephrotoxicity of several highly active antiretroviral (HAART) medications [10][11][12][13][14] . Kidney disease in HIV infected patients is associated with increased complications and utilization of health care resources [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a correlation between IDV nephrotoxicity and low body weight (11,18). This can be attributed * to a reduction in distribution volume, probably leading to higher IDV concentrations in such patients.…”
Section: Discussionmentioning
confidence: 94%
“…The risk factors associated with urological symptoms or renal injury during treatment have been already identified (7,9,11,18). Nevertheless, few clinical studies have been performed to investigate the mechanisms of reduction in renal function in patients receiving longterm treatment with IDV.…”
Section: Discussionmentioning
confidence: 99%